Isoform specific expression of ∆9 desaturases in two brain regions of common carp - Balla, Beáta; Hermesz, Edit (Acta Biologica Szegediensis, 2009)
An appropriate ratio of saturated and unsaturated fatty acids contributes to membrane fluidity. The ∆9 stearoyl-CoA desaturases are key enzymes involved in the regulation of the lipid composition of cellular membranes. The expressions of the ∆9 stearoyl-CoA desaturase genes are regulated by many environmental factors, such as temperature changes and metal exposure, mostly at the levels of transcription and mRNA stability. The present study analyzes the effects of cold shock and Cd2+ treatment on the regulation of two ∆9 desaturase genes in the olfactory lobe and the cerebellum of common carp. The effect of Cd2+ was also followed on the expressions of the ∆9 desaturase genes of cold-shocked animals. Sudden cold shock or Cd2+ exposure induced ∆9 desaturase expressions in a time-, brain region- and isoform-specific man-ner. In contrast, both ∆9 desaturase genes were repressed by Cd2+ in cold-shocked animals.